277. Comparison of Oral Beta-Lactams and Fluoroquinolones for Step-Down in Uncomplicated Enterobacterales Blood Stream Infections. (31st December 2020) - Ngo, Nichol; Sielatchom-Noubissie, Lionel; Molina, Kyle; Johnson, Tanner M; Huang, Misha; Hojat, Leila S; Kiser, Ty; miller, matthew
Abstract: Background: Bloodstream infections (BSI) with Enterobacterales (formerly Enterobacteriaceae ) group organisms are a frequently encountered complication, often stemming from urinary tract infections. Recent studies have demonstrated similar outcomes among patients transitioned to oral antibiotics compared to those managed solely with parenteral routes; however, most transitions utilize highly bioavailable agents such as fluoroquinolones (FQ). With limited comparative evidence on oral b-lactams (OBL) and mounting concerns over FQ safety and resistance, we sought to compare outcomes of FQ vs. OBL for Enterobacterales BSI step-down. Methods: Single-center, retrospective cohort of adults at University of Colorado Hospital from 2015–2017 with uncomplicated Enterobacterales BSI who stepped down to OBL or FQ after initial parenteral therapy. Exclusions were: pregnant or incarcerated, causative organism identified as Salmonella spp., Enterobacter spp., Citrobacter freundii, Serratia spp. and/or Klebsiella aerogenes, parenteral antibiotic duration ≥ 5 days, death before day 5, total antibiotic duration < 5 days or > 21 days. Primary outcome was clinical failure, a composite of any of the following within 30-days of antibiotic completion: death, recurrence or antibiotic change for presumed failure, or readmission for original infection. Results: Overall, 74 patients were included (n=36 OBL, n=38 FQ). Baseline characteristics were not different between groups, with overall mean age (SD) 60 (17) years and 62% female. E. coli was most commonly identified (65%), with 70% originating from the urinary tract. ICU admission was present in 18%, and median (IQR) Pitt Bacteremia Score was 2 (1–3). Treatment failure occurred in 25% OBL vs. 24% FQ recipients, p=0.55. No deaths were identified in either group within 30-days, and adverse events were rarely reported in either group. Multivariable analysis identified presence of nephrostomy tubes (OR 8.1; 95% CI: 1.1–61) but not OBL (OR 1.5; 95% CI: 0.3–7.2) as associated with clinical failure. Conclusion: In a cohort of uncomplicated Enterobacterales BSIs there does not appear to be a difference in clinical failure associated with OBLs compared to FQs. Additional studies with a larger cohort, or prospective trials are needed to confirm these findings. Disclosures: matthew miller, PharmD, Allergan (Speaker's Bureau)Tetraphase (Speaker's Bureau)